Management and Impact of SISPALA Extracurricular Activities for Kindergarten Students - Danil, Muhammad; Lubis, Saiful Akhyar; Mesiono, Mesiono; Pasaribu, Selamat (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This research aims to analyze the planning, implementation, and evaluation of SISPALA extracurricular activities at Kindergarten Aulia. This research was carried out using qualitative descriptive methods at the Aulia Medan Tembung Kindergarten from June to December 2024. The research subjects were the Head of the Madrasah/SISPALA Supervisor, the Deputy Head of the Madrasah for Student Affairs, teachers, parents, and students. Data collection was carried out through triangulation of sources and methods to increase research credibility. This research highlights the effectiveness of SISPALA activities in increasing students' environmental awareness and practical skills from an early age, as well as integrating extracurricular activities with the academic curriculum. The research results show that SISPALA planning is designed to support academic learning and increase environmental awareness. Implementation includes regular meetings, waste bank management, and reforestation projects. Evaluations are carried out regularly to ensure program effectiveness, improve the quality of activities, and support student character development. The implications of this research can be a reference for educational institutions in developing effective environment-based extracurriculars and for academics and practitioners in designing similar activities to improve student's learning experiences.